Prognostic significance of free triiodothyronine levels in alpine region patients undergoing drug-coated balloon therapy for coronary heart disease - Qin-Bao Zhang; Gang Wu; Ze-Ying Wang; Zhi-Liang Cui; Hong-Xia Zhang (Journal of Cardiothoracic Surgery)
Abstract Objective This study retrospectively analyzed the relationship between serum-free triiodothyronine (FT3) levels and the prognosis of coronary atherosclerotic cardiopathy (CHD) in patients from alpine regions treated with drug-coated balloons (DCB). Methods Data from 201 CHD patients with DCB at Hulunbuir People’s Hospital between September 2019 and August 2023 were included. Patients were divided into two groups based on the occurrence of major adverse cardiovascular events (MACE) after surgery. Univariate and multivariate logistic regression analyses were conducted to identify risk factors. The predictive efficiency of these risk factors for MACE was evaluated using the ROC curve. Results The poor prognosis group had significantly higher ages, a greater proportion of patients with a history of previous coronary interventions, and elevated levels of N-terminal pro-B-type natriuretic peptide compared to the good prognosis group. In contrast, FT3 levels were significantly lower (P < 0.05). No significant differences were observed in surgical parameters such as DCB target lesion site, lesion length, or puncture approach between the groups (P > 0.05). Multivariate binary logistic regression analysis identified FT3 level as an independent predictor factor of MACE in CHD patients treated with DCB. The optimal cut-off value for FT3 in predicting adverse prognosis following DCB surgery was 3.30 pmol/L, with a sensitivity of 72.5%, specificity of 62.8%, and an area under the curve (AUC) of 0.741 (P < 0.05). Conclusion Decreased FT3 levels serve as a biomarker for predicting the occurrence of MACE in patients from alpine regions undergoing DCB treatment for CHD. There is a significant correlation between reduced FT3 levels and the incidence of MACE in these patients.